Does Early Postoperative Rehabilitation Affect Pain, Function, and Satisfaction for Patients Underwent Microvascular Lower Limb Free Flap? - Sayed, Marwa Abd Elhamed; Mohammed, Magda Ahmed; Elsayed, Amr; Abdelmowla, Rasha Ali Ahmed (International Journal of Membrane Science and Technology, 2023)
Background: Microvascular free flap is an important to reconstructive tissue defects and restore anatomical structure and functional following disabling injuries. Aim of study: Evaluate the effect of early postoperative rehabilitation on patients’ pain, function, and satisfaction. Patients and Methods: Sixty patients who attended the microvascular reconstruction unit and the trauma department with lower limb defects indicated for microvascular free flap were randomly selected, their age (18 to 65 years). Sample were randomized into two groups by using a shuffled deck of cards (even number = control group, odd number = study group). Patients of the study group received an early postoperative rehabilitation teaching booklet while those of control group received regular hospital care only. Tool I: Patient assessment sheet. Tool II: Numeric pain rating scale. Tool III: Lower extremity functional scale. Tool V: Surgical satisfaction questionnaire. Results: Statistically significant difference was found in both groups concerning postoperative pain, lower limb function, and patients’ satisfaction during follow up (3 weeks, 3 months,6 months). Conclusion: Early postoperative rehabilitation protocol for patients who underwent microvascular lower limb free flap improved outcomes; significantly minimized pain level, improved lower limb function, and increased patients’ satisfaction. Recommendations: Early postoperative rehabilitation protocol for study group had a favorable effect on patients’ pain, function, and satisfaction. Patients who underwent microvascular lower limb free flap should receive careful early rehabilitation protocol to improve their outcomes.